Harnessing the Interactions of Wound Exudate Cells with Dressings Biomaterials for the Control and Prognosis of Healing Pathways - Shirin Saberianpour; Gianluca Melotto; Lucy Redhead; Nadia Terrazzini; Jaqueline Rachel Forss; Matteo Santin (MDPI AG, 2024)
The global socioeconomic challenge generated by wounds requires an understanding of healing and non-healing pathways in patients. Also, the interactions occurring between the wound dressing biomaterials with cells relevant to the healing process have not been sufficiently investigated, thus neglecting the role that wound dressing composition can play in healing. Through the study of six cases of acute surgical wounds, the present work analyses the early (24 h post-surgery) interactions of biochemical and cellular components with (i) Atrauman, a device made of knitted woven synthetic polymeric fibre when used as a primary dressing, and (ii) Melolin, a hydrocolloid engineered as two layers of synthetic and cellulose non-woven fibres when used as a secondary dressing. A pathway towards healing could be observed in those cases where endoglin-expressing cells and M2 macrophages were retained by Atrauman fibres at the interface with the wound bed. On the contrary, cases where the secondary dressing Melolin absorbed these cell phenotypes in its mesh resulted in a slower or deteriorating healing process. The data obtained indicate that a subtraction of progenitor cells by Melolin may impair the healing process and that the analysis of the retrieved wound dressings for biomarkers expressed by cells relevant to wound healing may become an additional tool to determine the patient's prognosis.